(untitled) (Issues in Social and Environmental Accounting (ISEA), 2015)
This study seeks to explore the crucial part in EMS implementation; i.e. environmental aspects and impacts, Good Environmental Practice to be developed in construction site, as well as the level of awareness or understanding amongst site staffs on ISO 14001 EMS implementation in their organizations. Data were collected via interviews, surveys and site visits. A number of environmental aspects and impacts, and Good Environmental Practices based on ISO 14001:2004 have been identified. The level of understanding of the site staffs on ISO 14001 EMS requirements has been found to be good except for matters concerning Schedule Waste Management. In conclusion, the successful implementation of ISO 14001 EMS mainly de pends on staffs‘ understanding.